Clotting Compass - Quick, Armand J (Thrombosis and Haemostasis, 1959)
A diagram has been devised based on a battery of tests, the results of which are recorded as points on a compass. The tests employed are described. The clotting pattern of various hemorrhagic diseases are presented and discussed.